Modalities in English and Vietnamese offers / Hồ Thị Minh Thái; NHDKH Supervisor: Assoc.Prof. Dr. Hoang Tuyet Minh - Hồ, Thị Minh Thái
Natural languages offer speakers many and various linguistic devices to facilitate their communication. It can be said that modalities play an important part in communicating activities. This study investigates how speakers of English and Vietnamese express the modal meaning in different offering strategies in terms of linguistic means. It attempts to seek what are the similarities and differences of the modal tools in English and Vietnamese offers. Data used in this study are collected from various sources of textbooks, literature works, internet, especially English practical textbooks, articles, and novels, stories in English and Vietnamese. To obtain the main objective of the study which is to show the similarities and differences of the modal tools in the two languages, we take examples in both English and Vietnamese into consideration. The results show that in offers, both two languages have three kinds of modal markers, which are lexical markers, grammatical markers, and prosodic markers. However, the usage of these markers is not the same in English and Vietnamese. This study wishes to help teachers and learners of English have more knowledge of modalities in English and Vietnamese offers when teaching and learning English. The most important thing is to help them improve their skills by providing some applications for teachers and learners.